Analisis Komparasi Potensi Kebangkrutan Model z-score Altman, Springate dan Zmijewski pada Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Hendarwati, Atik (Akmenika, 2014)
Bankruptcy prediction is one of the main issues in the classification of firms. Now a days, various models and researches are used for bankruptcy prediction. The purpose of this study is to present the theoritical bases of the research and com-pare the results obtained firm applying the Altman, Springate and Zmijewski mo-dels for firm bankruptcy prediction. Thus, we selected a sample of 12 food and be-verage manufacture companies, listed companies on Bursa Efek Indoinesia (BEI) and the data collected during the period 2009-2012 were tested. Multiple discri-minant analysis and Kruskal-Wallis non-parametric methods were applied for da-ta analysis. The result suggest that there is a significant difference between the three models in bankruptcy prediction.